2019
DOI: 10.1002/adma.201903125
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supporting, Flexible, Additive‐Free, and Scalable Hard Carbon Paper Self‐Interwoven by 1D Microbelts: Superb Room/Low‐Temperature Sodium Storage and Working Mechanism

Abstract: Hard carbon is regarded as a promising anode material for sodium‐ion batteries (SIBs). However, it usually suffers from the issues of low initial Coulombic efficiency (ICE) and poor rate performance, severely hindering its practical application. Herein, a flexible, self‐supporting, and scalable hard carbon paper (HCP) derived from scalable and renewable tissue is rationally designed and prepared as practical additive‐free anode for room/low‐temperature SIBs with high ICE. In ether electrolyte, such HCP achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(113 citation statements)
references
References 47 publications
2
104
0
Order By: Relevance
“…For instance, J. Jin et al 44 reported a reversible capacity of 275 mAh·g -1 while using a current density of 20 mA·g -1 and a mass loading of 1.8 mg•cm -2 , values which are almost two times lower than in our case. Hou et al 45 published indeed very good performance (i.e. ~335 mAh ·g -1 reversible capacity at 20 mA·g -1 ) but the mass loading used is extremely low, 0.9 mg•cm -2 .…”
Section: Hc-dmentioning
confidence: 99%
“…For instance, J. Jin et al 44 reported a reversible capacity of 275 mAh·g -1 while using a current density of 20 mA·g -1 and a mass loading of 1.8 mg•cm -2 , values which are almost two times lower than in our case. Hou et al 45 published indeed very good performance (i.e. ~335 mAh ·g -1 reversible capacity at 20 mA·g -1 ) but the mass loading used is extremely low, 0.9 mg•cm -2 .…”
Section: Hc-dmentioning
confidence: 99%
“…Insets show XRD pattern, a digital photo, TEM and Raman spectrum of the hard carbon paper anode. Reproduced with permission 123 . Copyright 2019, Wiley‐VCH…”
Section: Anode Materials For All‐climate Sibsmentioning
confidence: 99%
“…Hard carbon is often pre‐cycled in a half cell then applied as an anode in a full cell, which is difficult for real production. Hou et al 123 obtained a flexible, self‐supporting hard carbon paper from tissue (Figure 10C). In ether electrolyte (1 M NaCF 3 SO 3 in diglyme), the hard carbon paper anode achieved a high ICE (91.2%), superior high‐rate capability (170.0 mA h g −1 at 2000 mA g −1 ), as well as excellent capacity retention at low temperature.…”
Section: Anode Materials For All‐climate Sibsmentioning
confidence: 99%
“…Owing to the abundance, nontoxicity, safety, and durability, carbon-based anode materials that can satisfy the crucial characteristics of commercial electrodes are considered promising candidates for large-scale applications [16][17][18]. To date, a variety of carbon materials have been reported as anode materials for PIBs, such as graphite materials [19], graphene materials [26], hard carbon materials, and carbonbased composite materials [23].…”
Section: Introductionmentioning
confidence: 99%